SUPERhip Reconstruction Treatment in Patients with Congenital Femoral Deficiency of Paley's Classification Type 1b - Francisco Hélio Violante Júnior; Fernando Farcetta Júnior; Douglas Manuel Carrapeiro Prina; Monica Paschoal Nogueira (MDPI AG, 2024)
Background: Congenital femoral deficiency (CFD) is a challenging and complex condition that causes limb lengthening. We focused on the clinical and radiographic results of SUPERhip procedures in patients with congenital femoral deficiency type 1b, according to Paley's classification, prior to femoral lengthening. Methods: We reviewed all records and radiographs of patients who underwent this procedure between 2005 and 2020. We included 26 patients, with clinical and radiographic assessments performed during pre- and post-operative evaluations. Results: There were twenty-six patients (15 right vs. 11 left), with a mean age of 7 years (1-18). Most of the patients were female (17 patients; 65.4%). Twenty (76.9%) patients were undergoing their first procedure and six (23.1%) had already undergone a previous surgery. There was a significant improvement in all radiographic parameters, with the mean preoperative and postoperative Neck-Shaft Angle (NSA) being 72.3 ± 7.1° vs. 133.1 ± 12.7°, the Center-Edge Angle (CEA) 16.8 ± 9.8° vs. 33.5 ± 14.1°, and the Acetabular Index (AI) 27.8 ± 6.9° vs. 16.4 ± 6.8°, respectively. The complication rate was 15.4%, predominantly affecting patients under 5 years old. Conclusions: The SUPERhip procedure is an effective and reproducible technique for clinical and radiographic correction to a significant degree in patients with Paley's type 1b CFD, in preparation for bone lengthening surgery.